Multiple Exchange Rates, Fiscal Deficits and Inflation Dynamics - Bodart, Vincent (IMF Working Papers; Working Paper ;, 1996)
The paper explores the inflationary implications of exchange rate regime reforms in a small open economy model combining the public finance view of inflation with multiple exchange markets. To account for the experience of many developing countries, the analysis focuses on transitions to multiple official exchange markets. In those countries, multiple exchange rates were often announced as temporary. The paper shows that the dynamic response of inflation to the reform markedly differ whether the announcement is credible or not. The paper also compares the response of inflation under a fixed crawl of nominal official rates and under the presence of policy rules aimed at reducing the spread between the official and parallel exchange rates.